Chionodraco myersi DEWITT and TYLER ニ オイテ カンサツ サレタ セイテキ ニガタ ニ ツイテ - 岩見, 哲夫; イワミ, テツオ; 阿部, 宗明; アベ, トキハル; Iwami, Tetsuo; Abe, Tokiharu (1981)
P(論文) ロス海で採集したChionodraco myersi 49個体の外部形態の変異を調査した。同時に生殖巣の検査が可能な31個体に関しては, 肉眼もしくは組織学的所見に基づき性別を調べた。その結果, 第一背鰭最長棘条長の標準体長に対する割合が9.0%から30.0%と, かなりの変異を示した。雌と確認された23個体における第一背鰭最長棘条長の標準体長に対する割合は, 9.4%から16.3%, 雄と思われる8個体では22.5%から30.0%とふたつのグループに分離することができた。このことから, 第一背鰭最長棘条長における変異は, 性的二型現象と考えられた。Ch. myersiの雄の形態は, 1961年に記載されたChionodraco markhamiのそれときわめてよく似ており, この学名は, 1960年に記載されたCh. myersiの雄に付けられたものと考えられる。これまでにも, Ch. markhamiをCh. myersiのシノニムとする考えがあり, 本研究の結果はこの考えを支持する事実と思われる。 External morphological characters and sexes of Chionodraco myersi which was caught in the Ross Sea were examined. The relative length of the longest dorsal spine to the standard length of fish varied from 9.0% to 30.0% of the standard length. A histological observation revealed that twenty-three female specimens had the lower dorsal fin (9.4%∿16.3% of the standard length) and eight male specimens had the higher dorsal fin (22.5%∿30.0% of the standard length). As the morphological characters of the types of Chionodraco markhami resemble those of the "high dorsal" group, it seems that the species name of Ch. markhami should be given to males of Ch. myersi. The present results support the opinion that Ch. markhami is a synonymy of Ch. myersi. departmental bulletin paper